Study of management of appendicular abscess in children - Nandkishor Shinde; Ravindra Devani; Mohammed Abdul Baseer; Kiran Desai (Wolters Kluwer Medknow Publications, 2020)
Aim: To compare the outcomes in children who underwent emergency surgery and those who underwent percutaneous drainage for appendicular abscess. Materials and Methods: In this prospective study, 45 children of appendicular abscess detected on ultrasonogram (USG) were included in the study. The following characteristics were registered: age, gender, the time from onset of symptoms to seeking care, pain, vomiting, fever and general peritonitis; white blood cell count. The size, location of the abscess was noted on USG. After the diagnosis, we divided the patients into two groups based on the type of management. Patients who underwent emergency surgery and appendectomy (Group 1) which composed of twenty patients (14 males and six females) with their ages ranged from 3 to 18 years, and patients treated with ultrasound-guided percutaneous drainage and interval appendectomy (Group 2) which composed of 25 patients, (15 males and ten females) with their ages ranged from 2 to 18 years. Results: Group 1 included twenty patients and Group 2 included 25 patients. In Group 1, on USG the average size of the abscess was 7.2 ± 2.5 cm. After the surgery regained their functional recovery during a mean period of 3.2 ± 1 days. In Group 2, on USG average abscess size was 6.8 ± 2.4 cm. After the procedure regained their functional recovery on the second day. No major complications were noted in Group 2. On the contrary, 12 patients (60%) of Group 1 show complications in the form of wound infection in eight children and wound dehiscence in four children. Conclusions: USG-guided percutaneous drainage was safe and effective way of management of appendicular abscess.